Pelatihan Pembuatan Media Pembelajaran E-Learning Menggunakan Aplikasi Edmodo dalam Menunjang Proses Pembelajaran Bagi Guru-guru di SMA Negeri Titian Teras H. Addurrahman Sayoeti - Aprizal Lukman; Asni Johari; Desfaur Natalia; Ervan Johan Wicaksana (JPM: Jurnal Pengabdian Masyarakat, 2021)
The advancement of communication technology is very rapid, it has penetrated all areas of social, economic, cultural and educational life. In the field of education, communication technology is used to create a virtual learning system or LMS (Learning Management System) or better known as E-Learning. The use of E-Learning in the learning process can deliver a lot of main material with limited class time. One of the E-Learning used is Edmodo. The purpose of holding this training is to explain to SMA N Titian Teras teachers about the goals and benefits of learning with Edmodo. In addition, teachers are introduced to the features in Edmodo and provide knowledge on how to implement these features. The methods used in this service are lectures, discussions, guidance and training. It is hoped that with this training, the teachers of SMAN Titian Teras can understand and use Edmodo in the learning process, can apply the features that exist in Edmodo to facilitate the learning process. Keywords: Communication technology, e-learning media, Edmodo